Bibliometric Analysis of Research Trends on Differentiated Learning In Merdeka Curriculum - Muhdi Harto; Misbah Misbah; Desy Purwasih; Fadilah Umar; Nurlaela Muhammad (FKIP ULM, 2023)
This research employed bibliometric analysis which aimed to analyze differentiated learning research trends in the Merdeka Curriculum and visualize them. The database used was Google Scholar. Based on the search results with the keyword